Estimation of requirements to signal parameters at V-shaped frequency distribution in mathematical model of multi-position transmitter system - Kovalenko, A.I.; Titov, S.V.; Titova, E.V.; Cherna, O.S. (Radiotekhnika, 2022)
This paper is a brief review of methods for electromagnetic radiation focusing using a multi-position system of radiators based on mutually consistent spatial-amplitude-phase-frequency control of radiated signals and limitations of their potentialities arising from various random fluctuations of signals and antenna parameters. The statistical study of influence of different random and deterministic variations of electrical and design parameters of the antennas, control systems of the radiated signals with V-shaped frequency distribution over the aperture of a multi-position radiating system on the peak power level, duration and repetition period of the focused pulses is carried out. The parameters of the space-amplitude-phase-frequency control law must be stable for a time equal to the average duration of the pulses at the output of the emitters when forming a single space-time pulse, and when forming a sequence of space-time pulses during this pack of space-time pulses. The requirements concerning accuracy and stability of parameters of the signals’ space-phase-frequency control law are considered. The analysis of the influence of various kinds of deviations from the given values of the parameters of the space-phase-frequency control law of emitted signals in the channels of a multi-position system of emitters during formation of space-time pulses sequences is carried out. It is shown that the influence of errors in the location of the phase centers of the emitters in the direction of radiation does not depend on the distance to the focusing point, but is significant and special measures are required to reduce them.